Abnormal Breathing Patterns Predict Extubation Failure in Neurocritically Ill Patients - Pragya Punj; Premkumar Nattanmai; Pravin George; Christopher R. Newey (Case Reports in Critical Care)
In neurologically injured patients, predictors for extubation success are not well defined. Abnormal breathing patterns may result from the underlying neurological injury. We present three patients with abnormal breathing patterns highlighting failure of successful extubation as a result of these neurologically driven breathing patterns. Recognizing abnormal breathing patterns may be predictive of extubation failure and thus need to be considered as part of extubation readiness.